A Solution‐Processed All‐Perovskite Memory with Dual‐Band Light Response and Tri‐Mode Operation. (5th January 2022) - Guan, Xinwei; Wan, Tao; Hu, Long; Lin, Chun‐Ho; Yang, Jialin; Huang, Jing‐Kai; Huang, Chien‐Yu; Shahrokhi, Shamim; Younis, Adnan; Ramadass, Kavitha; Liu, Kewei; Vinu, Ajayan; et al.
Abstract: Integrating multiple semiconductors with distinct physical properties is a practical design strategy for realizing novel optoelectronic devices with unprecedented functionalities. In this work, a photonic resistive switching (RS) memory is demonstrated based on solution‐processed bilayers of strontium titanate (SrTiO3 or STO) quantum dots (QDs) and all‐inorganic halide perovskite CsPbBr3 (CPB) with an Ag/STO/CPB/Au architecture. Compared with the single‐layer STO or CPB RS device, the double‐layer device shows considerably improved RS performance with a high switching ratio over 10 5, an endurance of 3000 cycles, and a retention time longer than 2 × 10 4 s. The formation of heterojunction between STO and CPB significantly enhances the high resistance state, and the separation of the active silver electrode and the CPB layer contributes to the long‐term stability. More importantly, the photonic RS device exhibits UV–visible dual‐band response due to the photogating effect and the light‐induced modification of the heterojunction barrier. Last, tri‐mode operation, i.e., photodetector, memory, and photomemory, is demonstrated via tailoring the light and electric stimuli. This bilayer device architecture provides a unique approach toward enhancing the performance of photoresponsive data‐storage devices. Abstract : A solution‐processed photonic memory is fabricated using all‐perovskite SrTiO3 /CsPbBr3 bilayers as the switching media. The resistive switching performance of the device is considerably improved compared to the single‐layer counterparts, exhibiting response to dual UV–visible bands, as well as tri‐mode operation of photodetector, memory, and photomemory.